Factors Affecting Profitability of Insurance Companies in Ethiopia - Tadese Haile Wolde; Abiy Getahun Kolech; Mengistu Deyassa Dadi (Journal of International Trade, Logistics and Law, 2020)
The study was attempted to examine factors affecting profitability of insurance companies in Ethiopia for the period of 2014-2018, employed descriptive research design. The target populations were 17 insurance companies taken by census method. The study employed secondary sources of data from audited financial statement of National bank of Ethiopia. The study was used multiple regression models. The regression was run by using random effect model through Stata software version 14. The researchers found that the positive and significant relationship between ROA and liquidity, capital adequacy, real GDP as well as real effective exchange rate. Contrary, ROA has negative and significant relation with leverage, underwriting risk, premium growth. Besides, ROA has positive and insignificant relation with age and size whereas negative and insignificant relation with inflation. Thus, Insurance industry should give emphasis on liquidity ratio, and capital adequacy ratio to sustain its profitability.